Nilai Ekonomi Ikan Pelagis Hasil Tangkapan Nelayan Di Perairan Teluk Youtefa, Kota Jayapura - Tamara L.J. Kainama; Baigo Hamuna; Lisiard Dimara (ACROPORA: Jurnal Ilmu Kelautan dan Perikanan Papua, 2020)
Youtefa Bay is one of the coastal areas which is rich in fisheries and marine resources. The activity which commonly carries out at the Youtefa Bay is pelagic fish fisheries. Pelagic fish that is occurred in the waters of Youtefa Bay, has a high economic value which is adequate to comply with the income of society. The aims of this research were to determine the economic value of pelagic fish in the waters of Youtefa Bay, Jayapura City, Papua. This research was done from December 2018 to May 2019, located at Youtefa Bay, Jayapura City. The methods used were through field observation and interviews with the fishermen and society. The results of this research show that the pelagic fish in the Youtefa Bay dominated by small and medium fish. The pelagic fish which is found in the waters of Youtefa Bay has a high economic value. The types of pelagic fish, e.g. Caranx ignobilis, Caranx bartholomaei, Rastrelliger, Hemiramphus brasiliensis, Euthynnus affinis, Sardinella, and Scomberomorini.Key Words: Pelagic fish; Economic value; Papuan fisherman; Youtefa bay